A escola regular contemporânea e o aluno surdo/deficiente auditivo: dos modos de subjetivação para as singularidades produzidas no contexto das experiências escolares - Camillo, Camila Righi Medeiros (2020)
This Dissertation was carried out in the Graduate Program in Education of the Federal University of Santa Maria (PPGE/UFSM), in the Research Line of Special Education, Inclusion and Difference. Its main objective is to understand how the ways of being a deaf/hearing-impaired student have been produced in the contemporary regular school, considering school experiences in this context. The specific objectives are the following: to analyze the conditions of possibility for the emergence of the learning society in the neoliberal logic; to examine the displacement of the contemporary school from an emphasis on lifelong learning to an emphasis on the subjects’ unique experiences; to identify the school experiences that have emerged in the regular school as possibilities to resist the enterprise-school logic. Such propositions are in line with the methodological-theoretical field of the post-structuralist perspective in education, inspired by the Foucauldian Studies. The tool concepts of subjectification an experience have been put into operation from data produced in two regular schools of the public education system in Santa Maria (RS). The participants were three deaf/hearing-impaired students, teachers, special educators, managers and a mother, with whom narrative interviews, observations and dynamics were performed. A field journal was produced, and official school documents, such as the Pedagogical Political Project and the School Regulations, were analyzed. In addition to the analysis of the school routine, this Dissertation presents a selection of official documents in the areas of education and special education, with which I have attempted to understand to what extent the concept of learning society has spread in the world scenario over the last decades. This discussion has become necessary to both understand the effects of a certain regime of truth on certain forms of subjectification of the school subjects and enable a displacement to other ways of thinking about the school, its meanings and its subjects. Thinking of a school language and pedagogical possibilities that are not restricted to meeting either economic goals or the education of workers to be absorbed by the market demands is making sense of both the world and the fact of being in it. Thus, in the articulation between regular school, deaf/hearing-impaired students and school experiences, I think that subjectification processes produced in the singularities of the surveyed schools and their students have enabled me to defend the following thesis: in school experiences of/with deaf/hearing-impaired students with a more sensitive way of regarding their singularities, supported by pedagogical practices involving more empathy and respect for the others, I have identified possibilities of resistance to the content education, which has led to the production of subjects as machines intended for learning and being.